The long-run history of income inequality in Denmark: Top incomes from 1870 to 2010 - A. B. Atkinson; J.E. Søgaard (University of Copenhagen, Economic Policy Research Unit (EPRU), 2013)
We use historical publications and for more recent years micro-data from the income tax and wealth tax returns to estimate the development in income inequality in Denmark over the last 140 years. The paper breaks new ground in treating the specific features of the Danish Tax system and in analysing the implications of the switch from joint to individual taxation. We show that income inequality have declined substantially over the last century with an income share for the top 1 per cent dropping from 27.6 per cent from its peak in 1917 to 6.4 in 2010. However the decline is not simply a secular downward trend consistent with the downward part of a Kuznets curve. Instead there seems to be several distinct phases, interleaved with periods of stability.
Keywords: D31; H2; J3; N3; 330; Income inequality; Income distribution; Wealth distribution; Top incomes; Taxation; Denmark